Distribution profile of iridoid glycosides and phenolic compounds in two Barleria species and their correlation with antioxidant and antibacterial activity - Singh, Shachi; Kumar, Mukesh; Dwivedi, Seema; Yadav, Anjali; Sharma, Sarika (Frontiers in Plant Science, 2023)
Introduction Barleria prionitis is known for its medicinal properties from ancient times. Bioactive iridoid glycosides and phenolic compounds have been isolated from leaves of this plant. However, other parts of a medicinal plants are also important, especially roots. Therefore, it is important to screen all organs for complete chemical characterization. Method All parts of B. prionitis, including leaf, root, stem and inflorescence in search of bioactive compounds, with a rapid and effective metabolomic method. X500R QTOF system with information dependent acquisition (IDA) method was used to collect high resolution accurate mass data (HRMS) on both the parent (MS signal) and their fragment ions (MS/MS signal). ESI spectra was obtained in positive ion mode from all parts of the plant. A comparative analysis of antioxidant and antibacterial activity was done and their correlation study with the identified compounds was demonstrated. Principal component analysis was performed. Result Iridoid glycosides and phenolic compounds were identified from all parts of the showing variability in presence and abundance. Many of the compounds are reported first time in B. prionitis. Antioxidant and antibacterial activity was revealed in all organs, root being the most effective one. Some of the iridoid glycoside and phenolic compounds found to be positively correlated with the tested biological activity. Principal component analysis of the chemical profiles showed variability in distribution of the compounds. Conclusion All parts of B. prionitis are rich source of bioactive iridoid glycosides and phenolic compounds.